Forest fragmentation and selective logging affect the seed survival and recruitment of a relictual conifer - Brocardo, Carlos R. [UNESP]; Pedrosa, Felipe [UNESP]; Galetti, Mauro [UNESP] (Elsevier, 2018)
Defaunation, invasive species and forest fragmentation are considered to be the major drivers for the disruption of key ecological processes, particularly those related to plant animal-interactions such as seed dispersal and predation. The disruption of critical phases in the plant life cycle may ultimately have negative impacts on plant recruitment and the survival of plant populations. Here, for the first time we compared the seed removal and recruitment of Araucaria angustifolia, a critically endangered and relictual gymnosperm species, in multiple sites, including continuous and fragmented forest areas in the Brazilian Atlantic subtropical forest. Our sampling included seed removal experiment monitored by camera traps and surveys of A. angustifolia recruitment. We found that seed survival and recruitment were related to the density of adult A. angustifolia. Therefore the formation of large and dense groves, which is a characteristic of pristine Araucaria moist forests endangered by forest fragmentation and selective logging, may be an attempt to satiate seed predator communities. Additionally, forest fragmentation and the introduction of wild boar decreased seed survival to very low, and forest fragmentation decreased recruitment by fourfold on average. Increase protection and recuperation of Araucaria moist forests and the eradication of the invasive wild boar where possible are necessary measures for increasing seed survival rates and the recruitment of this relictual conifer.
Keywords: Araucariaceae; Cyanocorax chrysops; Dasyprocta azarae; Neotropics; Scatter-hoarding; Sus scrofa